LA INCLUSIÓN SOCIAL CON OPCIONES PRODUCTIVAS - Huaco Pastor, Enrique (2012)
Social inclusion is a concept that in a general area involves the process of incorporating social, economically, politically and culturally to the national community social groups excluded and vulnerable, in an operational area covers the notion of poverty and social inequality in a community, but is not limited to them. While poverty and social inequalities are an economic category that refers to the income of people, the concept of social inclusion includes other dimensions, including education, health, market entry, equity in opportunities involving welfare and development of the members of a community. We recognize that poverty category category brings social inequalities lack of integration of individuals with life and institutional resources of their environment. So it is evident the gap between urban to rural areas whose separation seems to draw the nuances of social exclusion among groups living within the same territory but nevertheless, differences lead to the breakdown of cultural ties and historical that bound. Our approach corresponds to the formulation of practical proposals relating to the reform and modernization of public institutions of central government, regional and local universities including powers for the promotion, organization and support of solidarity economy enterprises, designed based the establishment of production chains and cluster formation as a form of partnership and joint enterprise, in the form of enterprise networks.